A Comparative Study of Dexmedetomidine and Fentanyl on Airway Reflexes and Hemodynamic Responses to Tracheal Extubation in Nasal Surgeries - Saurabh Misra; Rajeev Tiwari; Shivendu Shekhar Ojha (Academia Anesthesiologica International, 2020)
Background: Extubation at light levels of anesthesia or sedation can stimulate reflex responses via tracheal and laryngeal irritation. The present study was conducted to compare dexmedetomidine and fentanyl on airway reflexes and hemodynamic responses to tracheal extubation in nasal surgeries.Subjects and Methods:The present study was conducted on 60 patients of ASA grade I and Grade II of both genders. Patients were divided into 2 groups of 30 each. Group I were dexmedetomidine 0.5 ?g/kg in 100 mL of isotonic saline and group II patients received fentanyl 1 ?g/kg in 100 mL of isotonic saline intravenously. Parameters such as duration of surgery and duration of anesthesia (minutes) were recorded. Extubation time, awakening time and orientation time was recorded.Results:The ASA grade I was seen in 20 in group I and 14 in group II, ASA grade II was seen in 10 in group I and 16 I group II. Group I comprised of 14 males and 16 females, group II had 17 males and 13 females. Mean duration of surgery in group I was 172.4 minutes and in group II was 174.6 minutes in group II. Mean duration of anesthesia was 194.2 minutes in group I and 198.6 minutes in group II. The difference was non- significant (P> 0.05). The mean extubation time in group I was 7.2 minutes and 5.6 minutes in group II, awakening time was 10.2 minutes in group I and 10.8 minutes in group II and orientation time was 14.3 minutes in group I and 15.2 minutes in group II.Conclusion:Authors found that dexmedetomidine 0.5 ?g/kg IV, administered before extubation, was more effective in attenuating airway reflex responses to tracheal extubation as compared with fentanyl 1 ?g/kg IV.